2020
DOI: 10.29333/ejgm/7869
|View full text |Cite
|
Sign up to set email alerts
|

Research on COVID-19 Virus Spreading Statistics based on the Examples of the Cases from Different Countries

Abstract: daily report, the epidemic of SARS-CoV-2 so far has caused 693224 cases and resulted in 33106 deaths in more than 200 countries. Referring to the data reported, World Health Organization declared the outbreak a pandemic. We considered the chain-binomial type of the model which involves short stages of high infectivity and approximately constant incubation periods. This research paper is to study and analyze the COVID-19 Virus spreading statistics on the examples of the cases from the different countries. High … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 11 publications
0
49
0
1
Order By: Relevance
“…It is worth noticing that many studies have considered very low recovery rate for the UK, for example Khafaie & Rahim (2020) has considered a recovery rate of 1.64% by 23 March 2020 in the UK. However, in the current study, due to the lack of available data on the recovery rate in UK, the global recovery rate of 53.38% is considered ( Gondauri, Mikautadze & Batiashvili, 2020 ). Therefore, the R 0 values can be estimated using the average R t value defined for different scenarios and the global recovery rate of 53.38%.…”
Section: Methodsmentioning
confidence: 99%
“…It is worth noticing that many studies have considered very low recovery rate for the UK, for example Khafaie & Rahim (2020) has considered a recovery rate of 1.64% by 23 March 2020 in the UK. However, in the current study, due to the lack of available data on the recovery rate in UK, the global recovery rate of 53.38% is considered ( Gondauri, Mikautadze & Batiashvili, 2020 ). Therefore, the R 0 values can be estimated using the average R t value defined for different scenarios and the global recovery rate of 53.38%.…”
Section: Methodsmentioning
confidence: 99%
“…COVID-19 was detected in December 2019 which later developed into a pandemic as it made an extensive change (Gondauri, Mikautadze, & Batiashvili, 2020) that affected not only Wuhan, China but all other countries around the globe. COVID-19 brought a plight into the sphere causing for health emergencies, socio-econmic recession, and academic disentanglement along the progression of the virus transmission.…”
Section: Introductionmentioning
confidence: 99%
“…The results found that sex, region, and infection reasons affected on both recovered and deceased cases, while birth year only affected on deceased cases. Gondauri et al (2020) considered the chain-binomial type of Bailey's model for studying and analyzing the correlation between the total volumes of COVID-19 virus spread and recovery from the different countries. Most of the study investigates the COVID-19 cases based on various regression and time series models because these models are frequently applied to examine the growth or trend of any disease.…”
Section: Introductionmentioning
confidence: 99%